Arbuscular mycorrhizal fungi in the soil using cover crops with and without nitrogen addition - Moura, Jadson Belem de; Ramos, Maria Lucrécia Gerosa; Konrad, Maria Luiza de Freitas; Saggin Júnior, Orivaldo José; Ribeiro Junior, Walter Quadros; Carvalho, Arminda Moreira de; Santos, Luana de Miranda; Souza, Rodrigo Fernandes de; Lopes Filho, Luiz César; Dutra e Silva, Sandro (Frontiers in Plant Science, 2022)
This study aimed to evaluate the occurrence of mycorrhizal fungi and glomalin contents in soil under different cover crops, with and without the application of Nitrogen in the cover. The following cover plants were used: Crotalaria juncea (Crotalaria juncea L.), wild beans from Ceará (Canavalia brasiliensis Mart. ex Benth.), Guandú 'BRS mandarin' [Cajanus cajan (L.) Millsp. ], Millet 'BR05' [Pennisetum glaucum (L.) R.Br.] and Sorghum 'BR 304' [Sorghum bicolor (L.) Moench]. The absolute control of the experiment was the treatment without the use of cover crops, that is, the vegetation of spontaneous occurrence in the area. The experimental design was randomized blocks in subplots, with three replications. Spore density, mycorrhizal colonization rate, easily extractable glomalin and species present in the rhizosphere of the cover crops were determined. No differences were found in the diversity of mycorrhizal fungi associated with the different cover crops studied or in the values of spore density, root colonization and glomalin content. Nitrogen application did not influence the mycorrhizal activity in the investigated cover crops. The most frequent species associated with cover crops were Scutellospora pellucida and Scutellospora persica in Crotalaria juncea; Gigaspora sp. on Sorghum; Glomus macrocarpum in Guandu; Glomus macrocarpum and Glomus clavisporum in Millet; and Glomus microaggregatum and Glomus tortuosum in Spontaneous Vegetation.